Massive localised lymphoedema: a rare vascular malformation. (12th June 2013) - Williams, K J; Al-Sakkal, M N; Alsafi, A; Davies, A H
Abstract : Lymphatic malformations are a subset of congenital vascular malformations, and are caused by a defect in lymphatic development during embryogenesis. When lymphatic mesoderm development is prematurely arrested, it retains it proliferative potential. Stimulus in the future can cause the lesion to proliferate locally without coordination or regulation, resulting in the rare condition known as massive localised lymphoedema (MLL). We present a case report of MLL, a rare and ill-defined soft tissue mass reported in the morbidly obese, with reference to the existing literature.